Relationship between Risk Factors and the Incidence of Hypertension in Pregnancy - Lilik Darwati; Khusnul Nikmah; Ikfina Nur Afiyah (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2023)
Hypertension in pregnancy is one of the causes of maternal death. Severe preeclampsia is the most significant cause of complications that can lead to death. This study aims to determine the factors that influence the incidence of hypertension in pregnancy. This was an analytical observational study with a case control approach. The study population was all pregnant women, with a total sample of 47 pregnant women, who were selected using a purposive sampling technique based on inclusion criteria. Data were collected using a questionnaire that had been tested for validity and reliability. Data were analyzed using the Chi-Square statistical test. This study was conducted among pregnant women at the Obstetrics and Gynecology Polyclinic of Ngimbang Regional General Hospital in Lamongan. Based on the results of statistical test using the Chi Square Test, it was obtained a p value equals 0.000 (P less than 0.05) which indicated that there was a relationship between history of hypertension and the incidence of Hypertension in pregnancy. The OR value of 262.857 indicated that a woman with a history of hypertension had 262.857 times higher risk to have hypertension in pregnancy. It can be concluded that hypertension in pregnancy was caused by factors of history of hypertension and coffee consumption habit. Pregnant women are recommended to avoid risk factors for hypertension in pregnancy. Furthermore, healthcare workers are expected to provide counseling and health education for early detection of pregnant women so as to prevent the risk factors for hypertension